Assessing Welfare Effects of the European Choice Agenda: The case of health care in the United Kingdom - Valentina Zigante (London School of Economics and Political Science (LSE), European Institute, 2011)
Choice and competition policies in public services are popular reform strategies in the member states of the European Union (EU). The European choice agenda is based on the view in the EU of 'social policy as a productive factor' and the need for 'modernisation' of the EU welfare states. This user-led, consumer oriented approach highlights the need to understand the effects of the choice and competition policies in public service. In conventional welfare economic the focus lies on analysis of efficiency, quality and equity effects and the current empirical evidence show varying results. This paper discusses choice policies in European countries and uses the case of choice in health care in the UK is to assess the welfare effects of choice and competition. The UK has a highly developed consumerist policy, and as it has served as a role model for other European countries implementing choice policies. The welfare effects are assessed using satisfaction with the NHS and subjective well-being as an indicator of individual welfare, gained from the introduction of choice of hospital in 2006. Further the equity aspect of choice is assessed by analysing variation in welfare effects between socio economic groups. The results indicate positive effects of choice, particularly for middle class individuals.
Keywords: 330